2021
DOI: 10.1111/mcn.13248
|View full text |Cite
|
Sign up to set email alerts
|

Using cognitive interviewing to bridge the intent‐interpretation gap for nutrition coverage survey questions in India

Abstract: Designing survey questions that clearly and precisely communicate the question's intent and elicit responses based on the intended interpretation is critical but often undervalued. We used cognitive interviewing to qualitatively assess respondents' interpretation of and responses to questions pertaining to maternal and child nutrition intervention coverage. We conducted interviews to cognitively test 25 survey questions with mothers (N = 21) with children less than 1 year in Madhya Pradesh, India. Each questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The findings of the study conducted by Domanska et al (2018) support the conclusion that adolescents lacked familiarity with certain terms in the questionnaire and required additional practical experience in healthcare interaction and disease prevention tasks [ 29 ]. Another comparable study concluded that using technical words in survey questionnaires could result in issues with understanding [ 42 ], although to a lesser extent than in this study. Identifying and addressing these issues related to questionnaires and respondents is recognized as crucial for increasing the accuracy and reliability of survey instruments.…”
Section: Discussionmentioning
confidence: 53%
“…The findings of the study conducted by Domanska et al (2018) support the conclusion that adolescents lacked familiarity with certain terms in the questionnaire and required additional practical experience in healthcare interaction and disease prevention tasks [ 29 ]. Another comparable study concluded that using technical words in survey questionnaires could result in issues with understanding [ 42 ], although to a lesser extent than in this study. Identifying and addressing these issues related to questionnaires and respondents is recognized as crucial for increasing the accuracy and reliability of survey instruments.…”
Section: Discussionmentioning
confidence: 53%
“…A previous nutrition coverage study in India reported that surveys noted challenges with long questions that had multiple concepts, with respondents missing the intention of the question [ 29 ]. Similarly in our study, long questions with multiple concepts or with two or more questions within the same sentence caused difficulty to some participants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that have noted the contrast between parents’ and professionals’ concerns have indicated the difficulty of getting parents to understand the concepts and terminology related to child nutrition as used by professionals [ 12 , 32 , 34 ]; for example, understanding growth through height and weight measurements [ 38 ] and the importance of continuous life care from beginning before childbirth to childhood. [ 39 ] It should be noted that although many parents obtain childcare support information from the Internet, they may not be receiving it from childcare professionals [ 40 ]. Parents may not recognize how many sweet beverages their children are drinking because they have insufficient knowledge of nutritional balance.…”
Section: Discussionmentioning
confidence: 99%